1987
DOI: 10.1007/bf02549303
|View full text |Cite
|
Sign up to set email alerts
|

cis‐Vaccenic acid in pulp lipids of commonly available fruits

Abstract: Fatty acids of commonly available fruit pulps have been analyzed by capillary gas chromatography of their methyl esters and by gas chromatography-mass spectrometry as their dimethyl disulfide adducts. The gas chromatographic and mass spectrometric data proved that these fruits always contained cis-vaccenic (cis-ll-octadecenoic) acid as a component fatty acid of their pulp lipids. The concentration of cis-vaccenic acid in total octadecenoic acids ranged from 1.9% to 95.1% in the fruit pulps examined. The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Another increased fatty acid is asclepic acid, usual in fruit pulp lipids (Shibahara et al 1987) and found in a small amount ± up to 3% ± in common vegetable seed oils. In analyses it is always added to the amount of oleic acid (Kleiman and Payne-Wahl 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Another increased fatty acid is asclepic acid, usual in fruit pulp lipids (Shibahara et al 1987) and found in a small amount ± up to 3% ± in common vegetable seed oils. In analyses it is always added to the amount of oleic acid (Kleiman and Payne-Wahl 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Palmitic, oleic and linoleic acids were the major components in all the lipids and lipid classes studied (Waheed et al, 2009 Lazos andServos (1988) andhabib et al (1986). Shibahara et al (1987) determined 11.7-21.5% palmitic, 1.0-1.7% stearic, 3.9-27.5% oleic, 3.9-22.3% cis-oleic, 18.0-36.2% linoleic and 7.2-16.0% linolenic acids in the pulp lipids of lemon, grapefruit, sweet orange and Japanese mandarin. Palmitic acid was found to be the dominant saturated fatty acid, but this fatty acid in Turkish citrus oil was in lower concentrations than those reported by French, 1962;Lazos and Servos, 1988;El-Adawy et al, 1999 andhabib et al, 1986.…”
Section: Chemical Evaluation Of Citrus Seeds An Agro-industrial Wastmentioning
confidence: 91%
“…cis-Vaccinate occurs at high levels (more than 10% of total fatty acids) in some seed oils (Chisholm antl Hopkins, 1965;Kleimari and Payne-Wahl, 1984), fruit pulp (Shibahara et al, 1986(Shibahara et al, , 1987Hibahara et al, 1989;Yamamoto et al, 19901, and tissue cultures of Hydnocarpus anthelminthica (Spencer et al, 1974) and Petroselinum crispum (Illlenbracht et al, 1980). However, in most plants (Chisholm and Hopkins, 1965;Mukherjee and Kiewitt, 19801, as well as mammals (Holoway and Wabil, 1964;Kuemmel and Chapman, 1968;Longmuir, 1987) and microorganisms (Fulco, 1983), it i s present in low concentrations (0.52%).…”
Section: Discussionmentioning
confidence: 99%